2015
DOI: 10.17957/ijab/15.0041
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effect of Integrated Nitrogen Management on Wheat Production in Acacia nilotica- and Eucalyptus camaldulensis-based Alley Cropping Systems

Abstract: Rapidly increasing population and shrinking farm resources are threatening the future of food security in developing countries. Under such conditions, development of agroforestry systems to meet the increasing demand of food, forage and wood is urgently needed. The objective of present research was to evaluate comparative effect of nitrogen management sources viz inorganic and organic on wheat production in Acacia nilotica-and Eucalyptus camaldulensis-based agroforestry systems established in saline environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Organic amendments, when applied in conjunction with inorganic amendments, can be more effective (Dargan et al 1976). Awan et al (2015) reported that application of farm yard manure alone or in combination with inorganic N fertilizer has significant effect on wheat yield on saline-sodic soil both under monoculture and in agro-forestry systems. The selection of the organic matter to be applied is very important in order to avoid causing N deficiency (adding an amendment which has too high C:N ratio) and also increase salinity (e.g., cow dung slurry).…”
Section: Use Of Organic Amendmentsmentioning
confidence: 99%
“…Organic amendments, when applied in conjunction with inorganic amendments, can be more effective (Dargan et al 1976). Awan et al (2015) reported that application of farm yard manure alone or in combination with inorganic N fertilizer has significant effect on wheat yield on saline-sodic soil both under monoculture and in agro-forestry systems. The selection of the organic matter to be applied is very important in order to avoid causing N deficiency (adding an amendment which has too high C:N ratio) and also increase salinity (e.g., cow dung slurry).…”
Section: Use Of Organic Amendmentsmentioning
confidence: 99%
“…Suriyan Cha-um and Chalermpol Kirdmanee (2011) reported that green manure mixed with FYM (Farm yard manure) increased the level of chlorophyll a and total chlorophyll pigments in RD6 (Oryza sativa L. spp. indica ) rice grown in saline soil (2% salt level).Use of compost, FYM and sesbania is useful for enhancing yield of rice-wheat production grown from salt affected soil environment , Awan et al, 2015. Tamarind, Pavetta indica, Thespesia, neem and sunn hemp were also effective against salinity and were used to improve the soil fertility (Vakeesan et al, 2008).…”
Section: Green Manure For Reclamation Of Salinitymentioning
confidence: 99%
“…Waste water of livestock contains high concentrations of ammonia nitrogen, organic and inorganic nitrogen compound, and pathogenic bacteria, reported that ground and surface water of Model Colony in which human activities associated with urbanization, mixing of sewage water in water reservoirs during rainy seasons, industrialization, and agricultural activities are extremely main sources of pollution (Gasim et al, 2009). Industrialization and emergence of urban units placed immense stress on water resources and discharge of wastewater into natural water resources that decreases ground and surface water quality (Awan et al, 2002). Most of the previous studies about water resources have focused on agriculture, the power industry, the petroleum refinery industry, the dyeing and finishing industry (Sanjrani et al 2019;Chen et al, 2016;Zhang et al, 2016;Sanjrani et al 2018;Bakken et al, 2016;Mughees et al, 2015;Takama et al, 1980).…”
Section: Introductionmentioning
confidence: 99%